Phytochemical Constituents and Pharmacological Activities of Sweet Basil-Ocimum basilicum L. (Lamiaceae) - Khan Marwat, Sarfaraz; Shoaib Khan, Muhammad; Ghulam, Said; Anwar, Naveed; Mustafa, Ghulam; Usman, Khalid; Rehman, Fazal-ur (Asian Journal of Chemistry, 2011)
Ocimum basilicum L. (sweet basil) belongs to family Lamiaceae. The family Lamiaceae comprises the most employed medicinal plants as a worldwide source of spices and also as a consolidated source of extracts. The chemical composition of sweet basil essential oil has been investigated and by now more than 200 chemical components have been reported from many regions of the world. The chemical constituents showed the presence of monoterpene hydrocarbons, oxygenated monoterpene, sesquiterpene hydrocarbons, oxygenated sesquiterpene, triterpene, flavanoids, aromatic compounds, etc. The compounds have been reported to exhibit antibacterial and antifungal, antiproliferative/anticancer, antidyspepsia, antigiardial, antiinflammatory, antioxidant, antiulcer, antiviral, insecticidal and wound-healing activities. They also showed antiwormal response, cardiac stimulant, effects on CNS, hypoglycaemic and hypolipidemic effects and inhibitory effect on platelet aggregation. Various parts of the plant of O. basilicum (sweet basil) have been widely used in traditional medicine. Leaves and flowering parts of O. basilicum are traditionally used as antispasmodic, aromatic, carminative, digestive, galactogogue, stomachic and tonic agent. They have also been used as a folk remedy to treat various ailments such as feverish illness, poor digestion, nausea, abdominal cramps, gastro-enteritis, migraine, insomnia, depression, gonorrhea, dysentery and chronic diarrhea exhaustion. Externally, they have been applied for the treatment of acne, loss of smell, insect stings, snake bites and skin infections.